Exogenous phytohormones enhance Paris polyphylla var. chinensis (Franch.) Hara biomass by regulating antioxidant systems and rhizosphere microbial subcommunities - Peng, Tong; Yang, Tao; Wang, Chengniu; Sha, Jie; Zhao, Jiang; Zhang, Lei (Frontiers in Plant Science, 2025)
IntroductionThe exogenous application of phytohormones is a widely adopted approach to enhance crop productivity. However, the precise regulatory effects of different phytohormones on plant antioxidant systems, rhizosphere microbial subcommunities (abundant, moderate, and rare), and their interactions with plant growth remain poorly understood.MethodsThis study explored the effects of melatonin (MT), strigolactone (SL), and 24-epibrassinolide (BR) on the phenotypic traits, physiological properties, and rhizosphere microbial subcommunities of Paris polyphylla var. chinensis (Franch.) Hara (PPC) through controlled pot experiments.ResultsOur study demonstrated that MT and SL significantly increased PPC biomass by 69.32% and 15.23%, respectively, whereas BR at 2 mg/L inhibited root development. MT and SL may influence the growth of PPC by modulating the antioxidant system. In addition, phytohormone treatments distinctly altered the structure of soil microbial subcommunities, with partial least squares path modeling (PLS-PM) revealing that MT exerted a dominant influence on PPC biomass by regulating the structure of abundant bacterial subcommunities. Furthermore, linear discriminant analysis effect size identified key microbial taxa associated with the application of phytohormones, further substantiating their roles in biomass enhancement.ConclusionThese findings provide significant insights into the ecological management of phytohormones for sustainable agricultural practices.